Strategi Pemuridan Untuk Menjaga Kemurnian Ajaran Kristiani Di Gereja Bethel Indonesi Jemaat Kingdom Worship Family Chruch Jayapura - Elfira Loppies; Yanto Paulus Hermanto (Publikasi Indonesia, 2025)
The spread of heretical teachings in the church today is a serious challenge to the purity of the faith of the church. Believers who lack a strong foundation of faith are easily susceptible to being influenced by teachings that deviate from the truth of God's word. True, structured and continuous discipleship is one of the main solutions to fortify the church from the influence of heretical teachings. This research aims to examine the role of discipleship in maintaining the purity of the faith of the church, as well as how biblical methods of discipleship are able to form disciples of Christ who are firm in doctrine and live according to the truth of the gospel. The research method used is a literature study with a theological qualitative approach, analyzing various literature, the Bible, theological books and research results related to discipleship and heretical teachings. The results of the study show that discipleship that focuses on faith building, healthy doctrinal teaching, supportive community, and the living example of spiritual leaders are very effective in countering heresy and maintaining the purity of the faith of the church. The church therefore needs to strengthen the discipleship system as an integral part of pastoral ministry.